2019
DOI: 10.1101/829028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural robustness affects the engineerability of aminoacyl-tRNA synthetases for genetic code expansion

Abstract: The ability to engineer the substrate specificity of natural aminoacyl-tRNA synthetase/tRNA pairs facilitates the site-specific incorporation of noncanonical amino acids (ncAAs) into proteins. The Methanocaldococcus jannaschii derived tyrosyl-tRNA synthetase (MjTyrRS)/tRNA pair has been engineered to incorporate numerous ncAAs into protein expressed in bacteria. However, it cannot be used in eukaryotic cells due to cross-reactivity with its host counterparts. The E. coli derived tyrosyl-tRNA synthetase (EcTyrR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Moreover, while general performance trends are expected to hold upon transferring ncAA incorporation systems between organisms, quantitative differences between organisms can occur, necessitating rigorous characterizations if further SPS implementation is performed in E. coli, mammalian cells, or cells from other organisms. 59,60 Despite these important considerations, our results provide several initial demonstrations that, in yeast, SPSs are a comparable format to DPSs. The indistinguishable ncAA incorporation measurements obtained from SPSs and DPSs suggest that SPSs could be advantageous for applications where the expression of both the OTS and POI are required, but selectable markers are limited.…”
Section: ■ Conclusionmentioning
confidence: 80%
“…Moreover, while general performance trends are expected to hold upon transferring ncAA incorporation systems between organisms, quantitative differences between organisms can occur, necessitating rigorous characterizations if further SPS implementation is performed in E. coli, mammalian cells, or cells from other organisms. 59,60 Despite these important considerations, our results provide several initial demonstrations that, in yeast, SPSs are a comparable format to DPSs. The indistinguishable ncAA incorporation measurements obtained from SPSs and DPSs suggest that SPSs could be advantageous for applications where the expression of both the OTS and POI are required, but selectable markers are limited.…”
Section: ■ Conclusionmentioning
confidence: 80%
“…This phenomenon is in line with our expectations because the decreased T m values of MbPylRS mutants (Figure S8) probably make them insufficient to maintain stable and thus be vulnerable to degradation at the physiological temperature. Collectively, these results emphasize the potential benefits of using a somewhat thermostable synthetase for enzyme engineering, 38,39 where sufficient structural robustness results in enhanced tolerance for potentially destabilizing but function-imparting mutations for altered substrate specificity.…”
Section: ■ Resultsmentioning
confidence: 71%
“…28,29 In addition, a chimera combining E. coli tyrosyl-tRNA synthetase and a thermophilic tyrosyl-tRNA synthetase exhibits higher activity at 37 °C than the wild-type progenitors, in addition to showing appropriate thermostability. 39 Inspired by these results, we were interested in finding out whether we could generate a more efficient chimeric PylRS mutant for enhanced eukaryotic GCE. Using the above-described thermostable PylRSs, we first generated two chimeric PylRSs by separately fusing the MtPylRS and Mf PylRS NTDs to the MbPylRS CTD (Figure 5a); the resulting chimeras are designated as tN-bC PylRS and fN-bC PylRS, respectively.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We recently reported that mutants of EcTyrRS often exhibit low thermostability. 32 In particular, pBPARS-1 was found to be largely insoluble under ambient conditions, which likely explains its poor activity. Interestingly, we found that a large fraction of pBPARS-3.1 is found in the soluble fraction of E. coli cell-free extract, while nearly all of pBPARS-1 is found in the insoluble fraction (Figure S4C).…”
Section: Resultsmentioning
confidence: 99%